The Effect of Buerger Allen Exercise on The Lower Extremity Peripheral Circulation in Type 2 Diabetic Patients - Muh Anwar Hafid; Ilhamsyah Ilhamsyah; La Ode Agustino Saputra; Mutmainnah Sari (Universitas STRADA Indonesia, 2021)
Prolonged elevated blood glucose levels leads to chronic microvascular complications, neuropathy complications and lower extremity peripheral circulation disorders. Actions that can be taken care in non-pharmacological that is Buerger Allen exercise.To determine the effect of Buerger Allen Exercise in lower limb peripheral circulation in diabetes mellitus patients.Study used a quantitative method with a pre-experimental design using a pre-post test without control group. Sampling technique is non-probability sampling with accidental sampling approach is obtained 5 respondents.The Wilcoxon Signed Rank Test results of the ABI value in the right limb are 0.043 or p <0.05 and the ABI value on the left limb are 0.025 or p <0.05.Buerger Allen Exercise is effective in improving peripheral circulation of the lower extremities and is an alternative for repairing impaired tissue perfusion in diabetic feet. Future research can examine the most appropriate frequency and duration.